Fields medallists' lectures - Atiyah, Michael Francis, 1929-2019; Iagolnitzer, Daniel (World Scientific series in 20th century mathematics, 2003)
Although the Fields Medal does not have the same public recognition as the Nobel Prizes, they share a similar intellectual standing. It is restricted to the field of mathematics and an age limit of 40 has become an accepted tradition. This volume presents contributions from Fields Medallists.